Rural transformation, empowerment, and agricultural linkages in Nepal - Raghunathan, Kalyani (International Food Policy Research Institute, 2019)
Presented by Kalyani Raghunathan (International Food Policy Research Institute), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.